Condizione femminile e sacramento dell'ordine: il ruolo della Commissione di studio sul diaconato delle donne: Prime ipotesi di ricerca - Abu Salem, Miriam (Donne, diritti e religioni, 2018)
The paper aims to investigate the role of the Study Commission on the Women's Diaconate established by Pope Francis in August 2016. In particular, the study suggests that women can be ordained deacons today. At least two main reasons can be used to support this hypothesis: an historical one which relies on the existence of women deacons in the ancient Church; a theological one which focuses on the relationship between the diaconate and the sacrament of order.